Pengaruh Penggunaan Digital Marketing dan Model Konvensional terhadap Peningkatan Jumlah Distribusi Penjualan Produk Unilever - Rahma, Khalda Faadiyah; Santoso, Sugeng (PANDITA: Interdisciplinary Journal of Public Affairs, 2026)
This study aims to examine the effect of digital marketing and conventional marketing on increasing the distribution sales of Unilever products in stores, agents, and stalls in Bekasi City. The research employed a descriptive quantitative approach using a survey method. The population consisted of partner retailers of PT Rukun Mitra Sejati Bekasi 1 within the company’s distribution area, with a total sample of 30 business units selected through purposive sampling. Data were analyzed using multiple linear regression, coefficient of determination, partial significance testing (t-test), and simultaneous significance testing (F-test). The results indicate that digital marketing has a strong and significant effect on distribution sales, as reflected by a t-value of 6.673 with a significance level of 0.000. Conventional marketing also shows a strong and significant influence on distribution sales, with a t-value of 6.420 and a significance level of 0.000. Simultaneously, both digital and conventional marketing variables demonstrate a very strong and significant impact on distribution sales, evidenced by an F-value of 24.071 with a significance level of 0.000. These findings highlight the strategic importance of integrating digital and traditional marketing approaches to improve distribution performance, particularly in small-scale retail sectors. This study provides practical insights for distributors and business practitioners in developing more effective and technology-adaptive marketing strategies to enhance sales performance.